A matched dual-tree wavelet denoising for tri-axial swallowing vibrations. (May 2016) - Dudik, Joshua M.; Coyle, James L.; El-Jaroudi, Amro; Sun, Mingui; Sejdić, Ervin
Abstract : Highlights: The dual-tree wavelet decomposition is more time-invariant for swallowing vibrations. The dual-tree wavelet decomposition removes more noise from swallowing vibrations. A wavelet matched to swallowing vibrations improves both attributes. Abstract: Swallowing disorders affect thousands of patients every year. Currently utilized techniques to screen for this condition are questionably reliable and are often deployed in non-standard manners, so efforts have been put forth to generate an instrumental alternative based on cervical auscultation. These physiological signals with low signal-to-noise ratios are traditionally denoised by well-known wavelets in a discrete, single tree wavelet decomposition. We attempt to improve this widely accepted method by designing a matched wavelet for cervical auscultation signals to provide better denoising capabilities and by implementing a dual-tree complex wavelet transform to maintain time invariant properties of this filtering. We found that our matched wavelet did offer better denoising capabilities for cervical auscultation signals compared to several popular wavelets and that the dual tree complex wavelet transform did offer better time invariance when compared to the single tree structure. We conclude that this new method of denoising cervical auscultation signals could benefit applications that can spare the required computation time and complexity.